Measurements of Ionic Structure in Shock Compressed Lithium Hydride from Ultrafast X-Ray Thomson Scattering - Kritcher, A; Neumayer, P; Brown, C; Davis, P; Doeppner, T; Falcone, R; Gericke, DO; Gregori, G; Holst, B; Landen, O; Lee, H; Morse, E; et al. (2009)
We present the first ultrafast temporally, spectrally, and angularly resolved x-ray scattering measurements from shock-compressed matter. The experimental spectra yield the absolute elastic and inelastic scattering intensities from the measured density of free electrons. Laser-compressed lithium-hydride samples are well characterized by inelastic Compton and plasmon scattering of a K-α x-ray probe providing independent measurements of temperature and density. The data show excellent agreement with the total intensity and structure when using the two-species form factor and accounting for the screening of ion-ion interactions. © 2009 The American Physical Society.